Perception on environmental pollution produced by objective advertising in Peru - Lahura Albujar, Nathalie E. (2021)
The perception of environmental pollution from objective public and private advertising in Peru was diagnosed. A 20-question semi-structured survey was used that was composed of three dimensions: primary information, environmental impacts and consequences, and control measures. The sample was 1,200 people and ran from May 20 to June 06, 2019. Respondents consider signs for political campaigns as the worst form of visual contamination. Graffiti has an environmental impact in cities, generating a terrible image. Digital propaganda signs generate impacts associated with glare and distraction of people, and posters are polluting elements. Advertising affects their concentration, and generates distraction causing their senses to alter, causing them to be in a bad mood and changes in their mood, and increases their stress levels. Also, they consider that visual contamination has an impact on their visual field. Advertising generates a bad image. For the dimension of control measures, they are in favor of implementing legal norms that regulate advertising, accompanied by audits to restrict exaggerated advertising. Advertising alternatives are digital and through social networks. Finally, it is concluded that the population considers advertising as elements of high visual impact, generating consequences with a potential effect on their health and the environment, generating a bad image for a city. The lack of legal norms and modern technologies at present generates an exacerbated publicity in the cities.